Factors associated with incident HIV infection versus prevalent infection among youth in Rakai, Uganda. Issue 1 (March 2015) - Edelstein, Zoe R.; Santelli, John S.; Helleringer, Stephane; Schuyler, Ashley C.; Wei, Ying; Mathur, Sanyukta; Song, Xiaoyu; Lutalo, Tom; Nalugoda, Fred; Gray, Ronald H.; Wawer, Maria J.; Serwadda, David M.
Abstract Factors associated with prevalent and incident HIV infection were compared among sexually experienced Ugandans aged 15–24. Most factors were similar. However, in women, older age and current marriage were associated with prevalent, but not incident, infection. It is important to recognize the limitations of prevalence analyses for identifying at-risk youth.